HUBUNGAN ANTARA TINGKAT STRES DAN ASUPAN MAGNESIUM DENGAN KEJADIAN DISMENORE PRIMER PADA REMAJA PUTRI DI SMA DAN SMK BATIK SURAKARTA - Hapsari, Zulaiha Anggi; Widiyaningsih, Endang Nur (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
This study aimed to determine the correlation between stress levels and magnesium intake with the incidence of primary dysmenorrhea in adolescent girls at Surakarta Batik High School and Vocational High School. The type of research used was observational with a cross-sectional approach. Sampling using simple random sampling technique with 192 research subjects. Data collection on stress levels was obtained through the Perceived Stress Scale questionnaire for the last 1 month. Magnesium intake data was obtained by filling out the SQ-FFQ form for the last 3 months. Data on the incidence of primary dysmenorrhea was obtained through the WaLIDD questionnaire for the past 1 month. The results showed that 91.7% of respondents experienced primary dysmenorrhea, 63.5% experienced moderate stress and 59.4% had good magnesium intake. Based on the chi-square test analysis, there is a correlation between stress levels and the incidence of primary dysmenorrhea (p-value 0.024), but there is no correlation between magnesium intake and the incidence of primary dysmenorrhea (p-value 0.184).